2017
DOI: 10.1002/minf.201700044
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome P450 3A4 has three Major Conformations: New Clues to Drug Recognition by this Promiscuous Enzyme

Abstract: Dedication: This paper is dedicated to the memory of Professor Boubekeur Maouche. Abstract:We computed the channels of the 3A4 isoform of the cytochrome P450 3A4 (CYP) on the basis of 24 crystal structures extracted from the Protein Data Bank (PDB). We identified three major conformations (denoted C, O1 and O2) using an enhanced version of the CCCPP software that we developed for the present work, while only two conformations (C and O 2 ) are considered in the literature.We established the flowchart of definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…These regions are bordered by putative SRSs (Substrate Recognition Site: see [70]). The flexibility of the F-F’ loop let us define three conformations of CYP3A4 [60]: the closed one, labeled C, and the opened conformations, labeled O1 or O2 depending, respectively, if block 1 or block 2 opens. Molecular dynamics simulations of cytochrome P450cam showed that substrates and products could egress from the active site via pathways in the vicinity of the three routes identified by TMP (thermal motion pathway) analysis, but with pathway 2 being energetically favored over pathways 1 and 3 [36,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These regions are bordered by putative SRSs (Substrate Recognition Site: see [70]). The flexibility of the F-F’ loop let us define three conformations of CYP3A4 [60]: the closed one, labeled C, and the opened conformations, labeled O1 or O2 depending, respectively, if block 1 or block 2 opens. Molecular dynamics simulations of cytochrome P450cam showed that substrates and products could egress from the active site via pathways in the vicinity of the three routes identified by TMP (thermal motion pathway) analysis, but with pathway 2 being energetically favored over pathways 1 and 3 [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The MCPs are clusterized. Each cluster defines a trajectory: it has surrounding atoms, residues and secondary structures [60]. Here, these trajectories correspond to channels, in the sense of [64].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Petitjean and his collaborators have analyzed 24 crystal structures of human CYP3A4 with their newly developed algorithm CCCPP (Computing Cavities, Channels, Pores and Pockets) [ 39 ] that finds out the different ways used by a cylinder to escape the catalytic cavity. They choose CYP3A4 because its numerous crystal structures are showing an impressive flexibility of some parts of the protein, suggesting that the ligand access and the exit routes might differ from a P450 structure to the next, and that these differences might be correlated to ligand physicochemical properties [ 71 ]. By doing so, they have classified the 24 crystal structures in three groups of different conformations, on closed, named C, in which a substrate-free CYP3A4 structure is found, and two open conformations, named O1 and O2.…”
Section: The F/g Region and Aromatic Residuesmentioning
confidence: 99%
“…Conversely, in structures of the inhibitor-bound (PDB: 3NXU) 52 and a substrate-bound form (PDB: 2J0D) of CYP3A4, 45 the Arg212 side chain points away from the active site and the I-helix (Figure 6C,D). As noted by Benkaidali et al, 53 movement of the F/F'-loop is also involved in the transition of CYP3A4 from the closed to the open state. Interestingly, in our HDX results with wild type CYP3A4, the F'helix, which is part of the putative allosteric site, is the least dynamic portion of the F-G region.…”
Section: Discussionmentioning
confidence: 78%